Understanding suicide's allure : steps to save lives by healing psychological scars /: steps to save lives by healing psychological scars. (2021) - Krippner, Stanley, 1932-; Joffe-Ellis, Debbie, 1956-; Paulson, Daryl S, 1947-; Riebel, Linda
No abstract available